Decent Work and Work Motivation in Knowledge Workers: the Mediating Role of Psychological Capital - Ferraro, Tânia (2018)
This article aimed to investigate the role of Decent Work as a predictor of different types of Work Motivation and to explore the possible role of Psychological Capital in mediating this relationship. The Decent Work Questionnaire, the Multidimensional Work Motivation Scale, and the Psychological Capital Questionnaire were administered to 3004 knowledge workers, in Portugal and Brazil. Results from Structural Equation Modeling analyses support the hypothesized model, showing the predictor role of Decent Work and complete and partial mediation effects of PsyCap in different relationships between Decent Work motivation variables. The results also support the idea that a decent work context predicts more autonomous work motivations again with the mediation of PsyCap. In sum, the results suggest that decent work plays an important role in promoting a positive approach to work, and that Psychological Capital is an important mediating variable in the promotion of autonomous Work motivation. Limitations and practical implications conclude the article.